Stocked rainbow trout (Oncorhynchus mykiss) affect space use by Warpaint Shiners (Luxilus coccogenis). Issue 1 (20th August 2018) - Elkins, Duncan; Nibbelink, Nathan P.; Grossman, Gary D.
Abstract: Due to widespread stocking, Rainbow Trout ( Oncorhynchus mykiss Walbaum) are perhaps the most widely distributed invasive species in the world. Nonetheless, little is known about the effects of stocked Rainbow Trout on native non‐game species. We conducted experiments in an artificial stream to assess the effects of hatchery Rainbow Trout on home range and behaviour of Warpaint Shiners ( Luxilus coccogenis Cope), a common minnow frequently found in stocked Southern Appalachian streams. We used the LoCoH algorithm to generate polygons describing the home ranges used by Warpaint Shiners. When a stocked trout was present Warpaint Shiners: (a) increased home range size by 57%, (b) were displaced into higher velocity mesohabitats, and (c) reduced mean overlap between the home ranges of individual warpaint shiners. Rainbow Trout did not significantly affect the edge/area ratio of Warpaint Shiner home ranges. Warpaint Shiner density (two and five fish treatments) did not significantly affect any response variable. Displacement from preferred microhabitats and increases in home range size likely result in increased energy expenditure and exposure to potential predators (i.e., decreased individual fitness) of Warpaint Shiners when stocked trout are present.